Rapid Response in a Patient with Relapsed/Refractory Multiple Myeloma Treated with BRAF/MEK Inhibitors - Otieno, Steve Biko; Nasir, Syed; Weir, Alva; Johnson, Robert (Case Reports in Hematology, 2020)
Patients with relapsed and refractory multiple myeloma have a poor prognosis. The mitogen-activated protein kinase (MAPK) pathway has been implicated in the pathogenesis of multiple myeloma. Several mutations in this pathway can lead to its constitutive activation leading to oncogenesis. One such mutation is BRAFV600E which is a therapeutic target in the treatment of melanoma, lung cancer, colon cancer, thyroid cancer, and hairy cell leukemia. BRAFV600E-directed therapy currently does not have approval in multiple myeloma. It has been proposed that this mutation leads to proteasome inhibitor resistance. About 4–10% of multiple myeloma cases harbor the BRAFV600E mutation. Herein, we report a case of a patient with relapsed and refractory multiple myeloma who had a progression-free survival (PFS) of 8.5 months on BRAF-targeted therapy.